Enfermería y medicina ancestral-tradicional en la atención materno neonatal - Madelyn Rosa Santillan Pineda (2023)
ABSTRACT: The objective of this research is to determine the knowledge of nursing and ancestral-traditional medicine in maternal neonatal care in the Health District 06D04 Colta Guamote, from September to December 2022, since that territory has a mostly indigenous population, bilingual kichwa, who have promoted from generation after generation respect for ancestral knowledge in the different life cycles, which have allowed it to be kept until today. Within primary health care, it is intended to strengthen intercultural health, through horizontal dialogues, exchange of knowledge, practices and attitudes of the ancestral-traditional, western and alternative system, in order to care for, protect pregnant women and the newborn, decreased mortality of the binomial. The methodology used was a quantitative, field, and cross-sectional study, as information collection instruments, two surveys were applied, previously validated by six fourth-level professionals, experts in the subject. The data was collected and processed in the Microsoft Office Excel version 2010 program and Microsoft Forms of office 365. The population consisted of 60 nursing professionals and 65 midwives. As results, a medium level of intercultural knowledge of the midwives regarding the care of the pregnant woman and the newborn is evidenced, guaranteeing the care of the pair through the identification of danger and alarm signs. , the importance of the frequency of prenatal check-ups, the care that must be provided to the newborn, immunizations in pregnant women and the neonate, but there are shortcomings in the identification of the names of the vaccines and the time for their administration. Keywords: health, intercultural, medicine, ancestral, midwives, care, maternal, neonatal